Modele eksperymentalne w procesie konstytuowania wiedzy medycznej - Rzepiński, Tomasz Marek (Filozofia Nauki, 2009)
The primary objective of this article is to analyse functions that experimental models have in the process of creating medical knowledge. When fulfilling this objective, we will refer to findings proposed by R. Harre and like this author; we will distinguish a special type of experimental models do called domesticated models. We will claim that constructing such models initiates three independent cognition activities undertaken in the process of establishing medical knowledge that is applied in clinical practice. Stabilisation of the model process is the first activity. Recognising this process is the second one and its extrapolation is the third one. Findings that we will make, will enable us to bring the process of establishing medical knowledge closer and point out at a category of problems that hinder the development of this process.